1993
DOI: 10.1111/j.1432-1033.1993.tb17784.x
|View full text |Cite
|
Sign up to set email alerts
|

Exchange reactions catalyzed by group‐transferring enzymes oppose the quantitation and the unravelling of the identity of the pentose pathway

Abstract: 1. The distributions and rates of transfer of carbon isotopes from a selection of specifically labelled ketosugar-phosphate substrates by exchange reactions catalyzed by the pentose and photosynthetic carbon-reduction-pathway group-transferring enzymes transketolase, transaldolase and aldolase have been measured using I3C-NMR spectroscopy.2. The rates of these exchange reactions were 5, 4 and 1.5 pmol min-' mg-' for transketolase exchange, transaldolase exchange and aldolase exchange, respectively.3. A compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Supporting evidence from the literature was presented, indicating that six additional reactions can take place [16][17][18][19]. Furthermore, van Winden et al [5] demonstrated that the incorporation of these reactions in the metabolic network model of Penicillium chrysogenum significantly increased the goodness-of-fit to measured 13 C-label distribution data and also resulted in a changed flux distribution.…”
mentioning
confidence: 78%
“…Supporting evidence from the literature was presented, indicating that six additional reactions can take place [16][17][18][19]. Furthermore, van Winden et al [5] demonstrated that the incorporation of these reactions in the metabolic network model of Penicillium chrysogenum significantly increased the goodness-of-fit to measured 13 C-label distribution data and also resulted in a changed flux distribution.…”
mentioning
confidence: 78%
“…4 [40, 64, 180]. One reason for those discrepancies might be that TK appears to catalyse exchange reactions much faster than the non-oxidative PPP¯ux rates [35].…”
Section: Sequence and Evolutionary Analysismentioning
confidence: 99%
“…Earlier studies attempted to assess OPPP activity by measurement of the reduction of label from [1-13 C]Glc in metabolic products by Glc 6-phosphate dehydrogenase reaction relative to the label from [6-13 C]Glc. However, refixation of the 13 CO 2 released and/or redistribution of label due to exchange reactions make such experiments difficult to interpret (Flanigan et al, 1993;Roscher et al, 2000).…”
Section: Glycolytic Breakdown Of Glc Dominates In Plastidic Acetyl-comentioning
confidence: 99%